FMRFamide-like peptides (FLPs) enhance voltage-gated calcium currents to elicit muscle contraction in the human parasite Schistosoma mansoni. - Ekaterina Novozhilova; Michael J Kimber; Hai Qian; Paul McVeigh; Alan P Robertson; Mostafa Zamanian; Aaron G Maule; Tim A Day (PLoS Neglected Tropical Diseases)
Schistosomes are amongst the most important and neglected pathogens in the world, and schistosomiasis control relies almost exclusively on a single drug. The neuromuscular system of schistosomes is fertile ground for therapeutic intervention, yet the details of physiological events involved in neuromuscular function remain largely unknown. Short amidated neuropeptides, FMRFamide-like peptides (FLPs), are distributed abundantly throughout the nervous system of every flatworm examined and they produce potent myoexcitation. Our goal here was to determine the mechanism by which FLPs elicit contractions of schistosome muscle fibers. Contraction studies showed that the FLP Tyr-Ile-Arg-Phe-amide (YIRFamide) contracts the muscle fibers through a mechanism that requires Ca(2+) influx through sarcolemmal voltage operated Ca(2+) channels (VOCCs), as the contractions are inhibited by classical VOCC blockers nicardipine, verapamil and methoxyverapamil. Whole-cell patch-clamp experiments revealed that inward currents through VOCCs are significantly and reversibly enhanced by the application of 1 microM YIRFamide; the sustained inward currents were increased to 190% of controls and the peak currents were increased to 180%. In order to examine the biochemical link between the FLP receptor and the VOCCs, PKC inhibitors calphostin C, RO 31-8220 and chelerythrine were tested and all produced concentration dependent block of the contractions elicited by 1 microM YIRFamide. Taken together, the data show that FLPs elicit contractions by enhancing Ca(2+) influx through VOCC currents using a PKC-dependent pathway.